Bridging the Understanding of Sustainability Accounting and Organizational Change. (March 2023) - Garcia-Torea, Nicolas; Larrinaga, Carlos; Luque-Vílchez, Mercedes
The role of sustainability accounting in promoting organizational change toward more sustainable practices is a relevant area of research for both accounting and organization studies. Despite the interdisciplinary nature of this topic, while accounting research was imagining and exploring the transformative potential of social and environmental accounting practices since the inception of this activity, scholars in organization studies have recently developed a more general interest in this matter. This article aims to review how the association between sustainability accounting and reporting and sustainable organizational change has been examined in both disciplines to elaborate on some potential bridges to foster the creation of an interdisciplinary research field around this association, where a fertile conversation could develop. The mapping of this literature prompts us to propose five bridges around: how accounting and reporting are conceived; the direction of causality between sustainability accounting and organizational change; the assemblage of explanatory factors; theoretical foundations; and research methods.